Efeito da simpatectomia provocada pela guanetidina sobre fêmures de ratas castradas - Mattos, Valéria Gonçalves Albieri (2005)
The bone sympathetic innervation influences the osteoblastic activity and supports the participation of Autonomic Nervous System on the bone formation regulation. Treatment with guanetidine promotes denervation of the sympathetic system in humans as well as animals. This work aims at investigating participation of the sympathetic system on the femur biology of ovariectomized adult rats. For this purpose, physical and biomechanical parameters, in addition to plasma and femur calcium were analyzed. Forty one, 4-month aged female Wistar rats were divided into the following experimental groups: basal (n=9), intact (n=8) treated with 1ml saline/Kg BW, castrated and treated with 1ml saline/Kg BW (n=7), castrated and treated with 37 mg guanetidine/Kg BW during six weeks (n=9) and castrated and treated with 40 mg guanetidine/Kg BW during eight weeks (n=8). The treatment was performed during six days/week. The animals were housed under controlled temperature (22 ± 1°C) and light (lights on between 8 a.m. and 6 p.m. daily) conditions. The rats had free access to food and tap water. After 8 weeks the animals were sacrificed. It was determined that ovariectomy induced higher BW gain and osteopenia. The denervation promoted by guanetidine did not protect the bone tissue from the deleterious effects on account of castration as demonstrated by the values of physical, biochemical and biomechanical parameters.